Determinants of Dividend Payout Ratios - A Study of the Indian Banking Sector - Rizvi, Saima; Khare, Sumi (Indian Journal of Finance, 2011)
In the present day world, all the decisions of firms are linked to the concept of wealth maximization of shareholders. Dividend policy is an integral part of a firm’s financing decision. The dividend payout ratio determines the amount of earnings that can be retained in the firm as a source of financing. At the same time, retaining a greater amount of current earnings in the firm means fewer rupees will be available for current dividend payments. A major challenge for any firm is to determine the optimal allocation of profits between dividend payments and addition to the firm’s retained earnings. The subject of corporate dividend has caught the attention of researchers for a long time, resulting in intensive theoretical modeling and empirical investigation. But several questions related to dividend decisions remain perplexing because of diverse and conflicting theories and also due to diverse empirical results. The purpose of this paper is to examine the factors which affect the dividend payout ratio of Indian Banks. A sample of banks from CNX BANKEX Index has been selected for the study. Statistical techniques of correlation and regression have been used to explore the relationship between key variables. The results of the study show positive and significant association between Earning per share (EPS) and Dividend Payout Ratio (DP). Thus, EPS is an important determinant of DP ratio with increase in EPS, the firm’s ability to pay dividend also increases. Stock beta has been found to have a negative but significant relationship with Dividend Payout Ratio in the banking sector. The results disclose insignificant relationship with cash flow from operations, debt equity ratio and tax to profit before tax ratio. However, the target payout ratio of the industry has declined to 44 percent in 2005-2006 from 71 percent in 1996-97. Dividend payout ratio has always been a topic widely researched in the area of Financial Management. This study would enable banks to identify the factors on which their dividend policy will depend. This is the first paper to study the determinants of dividend payout ratios of Indian Banking Sector using the BANKEX Index.